Transkingdom mechanism of MAMP generation by chitotriosidase feeds oligomeric chitin from fungal pathogens and allergens into TLR2-mediated innate immune sensing - Chang, Tzu-Hsuan; Cardona Gloria, Yamel; Hellmann, Margareta J.; Richardo, Timmy; Greve, Carsten Leo; Le Roy, Didier; Roger, Thierry; Bork, Francesca; Bugl, Stefanie; Jakob, Johanna; Sonnberger, Johannes; Kasper, Lydia; et al. (Frontiers in immunology, 2025)
IntroductionChitin is a highly abundant polysaccharide in nature and is linked to immune recognition of fungal infections and asthma in humans. Ubiquitous in fungi and insects, chitin is absent inmammals and plants and, thus, represents a microbeassociatedmolecular pattern (MAMP). However, highly polymeric chitin is insoluble, which potentially hampers recognition by host immune sensors. In plants, secreted chitinases degrade polymeric chitin into diffusible oligomers, which are “fed to” innate immune receptors and co-receptors. In human and murine immune cells, a similar enzymatic activity was shown for human chitotriosidase (CHIT1), and oligomeric chitin is sensed via an innate immune receptor, Toll-like receptor (TLR) 2. However, a complete system of generating MAMPs from chitin and feeding them into a specific receptor/co-receptor-aided sensing mechanism has remained unknown in mammals.MethodsThe effect of the secreted chitinolytic host enzyme, CHIT1, on the TLR2 activity of polymeric chitin preparations from shrimps, house dust mites and the fungal pathogen Candida albicans was assessed in vitro using cell lines and primary immune cells. Moreover, the regulation of CHIT1 was analyzed.ResultsHere, we show that CHIT1 converts inert polymeric chitin into diffusible oligomers that can be sensed by TLR1/TLR2 co-receptor/receptor heterodimers, a process promoted by the lipopolysaccharide binding protein (LBP) and CD14. Furthermore, we observed that Chit1 is induced via the b-glucan receptor Dectin-1 upon direct contact of immortalized human macrophages to the fungal pathogen Candida albicans, whereas the defined fungal secreted aspartyl proteases, Sap2 and Sap6, from C. albicans were able to degrade CHIT1 in vitro.DiscussionOur study shows the existence of an inducible system of MAMP generation in the human host that enables contact-independent immune activation by diffusible MAMP ligands with a striking similarity to the plant kingdom. Moreover, this study highlights CHIT1 as a potential therapeutic target for TLR2-mediated inflammatory processes that are fueled by oligomeric chitin.